C-terminal deletion analysis of plant plasma membrane H(+)-ATPase: yeast as a model system for solute transport across the plant plasma membrane. - Regenberg, B (1995)
The plasma membrane proton pump (H(+)-ATPase) energizes solute uptake by secondary transporters. Wild-type Arabidopsis plasma membrane H(+)-ATPase (AHA2) and truncated H(+)-ATPase lacking 38, 51, 61, 66, 77, 92, 96, and 104 C-terminal amino acids were produced in yeast. All AHA2 species were correctly targeted to the yeast plasma membrane and, in addition, accumulated in internal membranes. Removal of 38 C-terminal residues from AHA2 produced a high-affinity state of plant H(+)-ATPase with a low Km value (0.1 mM) for ATP. Removal of an additional 12 amino acids from the C terminus resulted in a significant increase in molecular activity of the enzyme. There was a close correlation between molecular activity of the various plant H(+)-ATPase species and their ability to complement mutants of the endogenous yeast plasma membrane H(+)-ATPase (pma1). This correlation demonstrates that, at least in this heterologous host, activation of H(+)-ATPase is a prerequisite for proper energization of the plasma membrane.